2017
DOI: 10.1002/adv.21835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blast furnace slag content on mechanical and slurry abrasion behavior of needle‐punched nonwoven fabric reinforced epoxy composites

Abstract: This article reports on mechanical and slurry abrasion response of a new class of material developed by reinforcement of blast furnace slag (BFS) in needle-punched nonwoven polyester fabric epoxy composites. These epoxy-based composites are prepared by the hand-lay-up technique with the variation of BFS content (0, 5, 10, and 15 wt. %) and at constant fiber loading. It is observed that the mechanical properties of the composites are improved significantly with the incorporation of filler.However, the propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It is also observed that the void fraction of fabricated composites increases from 0.79% to 3.88% as the filler content increases in the composites. The increased in void percentage with an increase in filler percentage may be due to the air entrapped at the interface of the composite constituents during the impregnation of the matrix 23,24 . Also, the filler material addition to epoxy imparts flow resistance and modifies curing characteristics of the matrix 25 …”
Section: Resultsmentioning
confidence: 99%
“…It is also observed that the void fraction of fabricated composites increases from 0.79% to 3.88% as the filler content increases in the composites. The increased in void percentage with an increase in filler percentage may be due to the air entrapped at the interface of the composite constituents during the impregnation of the matrix 23,24 . Also, the filler material addition to epoxy imparts flow resistance and modifies curing characteristics of the matrix 25 …”
Section: Resultsmentioning
confidence: 99%
“…Significant works are reported on use of fillers as effective reinforcements like fly ash cenosphere [9][10][11], hollow glass microballoon [12], rice husk [13][14][15], blast furnace slag [16,17], walnut shell powder [18,19], waste tire rubber [20][21][22], polymer microcapsules [23,24] etc. Waste tire rubber in particular has gained a significant research interest owing to the abundant availability.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative method to reuse and recycle most industrial and organic wastes, the application of polymeric composites with residues as reinforcement fillers has grown interest among the researchers. Composites using pineapple fiber (Pittayavinai, 2016), sugarcane bagasse fiber (Paiva, 2018), jute fiber (Huang, 2017), leather waste (Garcia, 2015), rice husk ash (Pongdong, 2016), blast furnace slag (Patnaik, 2018), phosphogypsum (Essabir, 2017), glass fiber (Novais, 2017), marble (Fiore, 2018), and mineral wool (Väntsi, 2014), have been widely reported. Among the polymers, research involving the use of natural rubber for artificial muscles (Hawkes, 2016), microfluidic matrix , antibacterial composites (Chen, 2018), green synthesis (Cabrera, 2013) and, solventsensitive memory materials (Dong, 2016) as well as the recycling of residues as fillers (Barrera, 2016) and (Zefeng, 2018) make the elastomer an interesting way to reuse clay brick residues.…”
Section: Introductionmentioning
confidence: 99%